1987
DOI: 10.3758/bf03197032
|View full text |Cite
|
Sign up to set email alerts
|

The influence of camera angle on comprehension and retention of pictorial events

Abstract: A subset offormal compositional principles was examined in the context of narrative pictorial events. Slide stories were constructed of six common events in which characters were depicted from three camera angles: low angle, eye-level, and high angle. After presentation, subjects evaluated the characters, recalled the stories, and engaged in a recognition task. Camera angle influenced subjects' evaluation and retention ofthe stories in accordance with aesthetic principles. Camera angle had significant, predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 26 publications
2
64
0
1
Order By: Relevance
“…Moore et al (1979) proposed that low ceilings may encourage quieter, more restricted play, while higher ceilings (e.g., above 8 feet) foster more active (i.e., freer) play. Echoing similar sentiments, Kraft (1987) posited that high, downward-looking camera angles, which tend to compress height, convey the notion of passivity; however, low, upward-looking angles, which accentuate height, connote action and thus freedom of movement. Thus, taken together, such research leads to the contention that relatively high versus low ceilings are likely to prime the concepts of freedom versus confinement, respectively.…”
Section: Ceiling Height and Type Of Processingmentioning
confidence: 99%
“…Moore et al (1979) proposed that low ceilings may encourage quieter, more restricted play, while higher ceilings (e.g., above 8 feet) foster more active (i.e., freer) play. Echoing similar sentiments, Kraft (1987) posited that high, downward-looking camera angles, which tend to compress height, convey the notion of passivity; however, low, upward-looking angles, which accentuate height, connote action and thus freedom of movement. Thus, taken together, such research leads to the contention that relatively high versus low ceilings are likely to prime the concepts of freedom versus confinement, respectively.…”
Section: Ceiling Height and Type Of Processingmentioning
confidence: 99%
“…Visual portrayal may matter most for products that reveal different features when viewed from different angles (cf. Kraft, 1987), features that may underlie the activation of different trait concepts, which in turn may differentially affect impressions. Multiple lines of research suggest that the automobile is one such product.…”
Section: Visual Portrayal and Product Impressionsmentioning
confidence: 99%
“…Camera angle did not significantly affect viewers' judgments of products when they were highly motivated to process the depicted material in detail. The authors suggested a heuristic processing explanation, formerly stated by Kraft (1987): Camera angle effects on judgments might be due to the use of simple decision rules or heuristics (i.e., objects that we visually look up to are more positive); when people are highly motivated, they form judgments by carefully weighting the perceived true merits of what they have been presented.…”
Section: Introductionmentioning
confidence: 99%
“…In three experiments, Kraft (1987) examined the extent to which manipulations of vertical camera angle can affect viewers' evaluations of characters in a story, viewers' recall of the characters and of the story as a whole, and viewers' recognition memory. Six four-pictures stories depicted each time two characters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation